2017
DOI: 10.1172/jci88502
|View full text |Cite
|
Sign up to set email alerts
|

Mutant α2-chimaerin signals via bidirectional ephrin pathways in Duane retraction syndrome

Abstract: Duane retraction syndrome (DRS) is the most common form of congenital paralytic strabismus in humans and can result from α2-chimaerin (CHN1) missense mutations. We report a knockin α2-chimaerin mouse (Chn1 abducens neurons use bidirectional ephrin signaling via mutant α2-chimaerin to direct growth, while cervical spinal neurons use only ephrin forward signaling, and trochlear neurons do not use ephrin signaling. These findings reveal a role for ephrin bidirectional signaling upstream of mutant α2-chimaerin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 45 publications
(84 reference statements)
3
25
0
Order By: Relevance
“…Although it is likely that the axon guidance mechanisms in the abducens nerve are different from those of other ocular nerves, the exact molecular mechanisms remain to be elucidated. Recently, Nugent et al reported that knock-in mice with an α2-chimerin gain-of-function missense mutation, identified in CCDD patients, showed a similar stalled phenotype in the abducens nerves, with variable penetrance [ 25 ]. More importantly, they also demonstrated that axons in α2-chimerin-knockout mice, a loss-of-function model, and mice with knockout of the upstream adhesion molecule, EphA4, exhibited the wandering phenotype in abducens nerves as also detected in our DINE mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is likely that the axon guidance mechanisms in the abducens nerve are different from those of other ocular nerves, the exact molecular mechanisms remain to be elucidated. Recently, Nugent et al reported that knock-in mice with an α2-chimerin gain-of-function missense mutation, identified in CCDD patients, showed a similar stalled phenotype in the abducens nerves, with variable penetrance [ 25 ]. More importantly, they also demonstrated that axons in α2-chimerin-knockout mice, a loss-of-function model, and mice with knockout of the upstream adhesion molecule, EphA4, exhibited the wandering phenotype in abducens nerves as also detected in our DINE mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…The specification of the abducens motor neurons relies on Hox-dependent positional values (Gaufo et al, 2003;Manzanares et al, 1997;Prince et al, 1998). Following specification, axons of abducens motor neurons are guided by extrinsic directional cues, including semaphorin and ephrin, through activation of downstream signaling pathways that modulate cytoskeletal dynamics (Ferrario et al, 2012;Nugent et al, 2017). Consistent with these molecular mechanisms, the causative genetic loci for Duane retraction syndrome (DRS), a congenital type of strabismus, encode transcription factors for hindbrain patterning (HOXA1 and MAFB) (Park et al, 2016;Tischfield et al, 2005) and a Rac-GAP modulating cytoskeletal dynamics (CHN1/a2chimaerin) (Miyake et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Following specification, axons of abducens motor neurons are guided by extrinsic directional cues, including semaphorin and ephrin, through activation of downstream signaling pathways that modulate cytoskeletal dynamics (Ferrario et al, 2012) (Nugent et al, 2017). Consistent with these molecular mechanisms, the causative genetic loci for Duane retraction syndrome (DRS), a congenital type of strabismus, encode transcription factors for hindbrain patterning (HOXA1 and MAFB) (Tischfield et al, 2005) (Park et al, 2016) and a Rac-GAP modulating cytoskeletal dynamics (CHN1/α2-chimaerin) (Miyake et al, 2008).…”
Section: Introductionmentioning
confidence: 99%